2020
DOI: 10.1001/jamaoncol.2020.0197
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Pathogenic Germline Variants in Cancer-Susceptibility Genes in Patients With Osteosarcoma

Abstract: the most common malignant bone tumor in children and adolescents, occurs in a high number of cancer predisposition syndromes that are defined by highly penetrant germline mutations. The germline genetic susceptibility to osteosarcoma outside of familial cancer syndromes remains unclear.OBJECTIVE To investigate the germline genetic architecture of 1244 patients with osteosarcoma.DESIGN, SETTING, AND PARTICIPANTS Whole-exome sequencing (n = 1104) or targeted sequencing (n = 140) of the DNA of 1244 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
147
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 180 publications
(168 citation statements)
references
References 91 publications
7
147
0
6
Order By: Relevance
“…7 Most recently, MSH2 was reported as one of a small number of genes that showed a significantly higher burden of pathogenic or likely pathogenic variants in European OS patients compared to controls (0.4%, 3 of 732 patients). 8 We conclude that the incidence of OS in LS patients is significantly increased compared to the general population. We suggest that osteosarcoma is part of the LS spectrum in adults and seems to be associated particularly with the path_MSH2 genotype.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…7 Most recently, MSH2 was reported as one of a small number of genes that showed a significantly higher burden of pathogenic or likely pathogenic variants in European OS patients compared to controls (0.4%, 3 of 732 patients). 8 We conclude that the incidence of OS in LS patients is significantly increased compared to the general population. We suggest that osteosarcoma is part of the LS spectrum in adults and seems to be associated particularly with the path_MSH2 genotype.…”
mentioning
confidence: 64%
“…Regarding the type of path_MMR variants identified in these patients, predicted missense changes were most common (7/16), followed by splicing (5/16) and deletion variants (4/16). Regarding gender, equal numbers of females (8) and males 8were affected.…”
mentioning
confidence: 99%
“…Compared to regular population incidences (0.34/100,000 for osteosarcomas [39] and 3.4/100,000 for soft-tissue sarcomas [40]), this indicates that osteosarcoma and soft-tissue sarcoma incidences are >50 timers and >1.8 times higher, respectively, in LS patients. Reinforcing this increased risk of osteosarcomas, recently Mirabello et al [41] investigated germline causes of 1244 patients with osteosarcoma and identified more germline MSH2 pathogenic variants in cases than in the control cohorts (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Four POT1 mutations were identified significantly more frequently in breast cancer patients ( n = 1067) than in healthy controls ( n = 1110) [ 101 ]. Moreover, in a recent study focusing on pathogenic osteosarcoma germline mutations, five POT1 germline variants (p.Asp42Tyr, p.Gln376Arg, p.Leu69Phe, p.Asp617fs; p. and c.670G > A) were detected ( n = 5/1004) [ 102 ]. In those with European ancestry, POT1 germline mutation frequency was statistically significantly enriched in those with disease (0.5%, n = 4/732), indicating a potential association between POT1 germline variants and risk of developing osteosarcoma [ 102 ].…”
Section: Germline and Somatic Pot1 Mutations Inmentioning
confidence: 99%
“…Moreover, in a recent study focusing on pathogenic osteosarcoma germline mutations, five POT1 germline variants (p.Asp42Tyr, p.Gln376Arg, p.Leu69Phe, p.Asp617fs; p. and c.670G > A) were detected ( n = 5/1004) [ 102 ]. In those with European ancestry, POT1 germline mutation frequency was statistically significantly enriched in those with disease (0.5%, n = 4/732), indicating a potential association between POT1 germline variants and risk of developing osteosarcoma [ 102 ]. Furthermore, one case–control study has shown that the presence of the rs10244817 variant in POT1 is significantly associated with lung cancer [ 103 ], and a single nucleotide polymorphism (SNP) near POT1 (rs116895242) is associated with a reduced likelihood of acquiring colorectal, ovarian, and lung cancer [ 104 ].…”
Section: Germline and Somatic Pot1 Mutations Inmentioning
confidence: 99%